Pengaruh Senam Persadia Seri 1 terhadap Penurunan Gula Darah Puasa Pada Wanita Diabetes Melitus di Puskesmas Banyu Urip, Surabaya - Farahiyah, Jihaan; Fatmaningrum, Widati; Mudjanarko, Sony Wibisono (Universitas Pahlawan Tuanku Tambusai, 2024)
Diabetes Mellitus is characterized by high blood sugar levels. High blood sugar levels stimulate pancreatic beta cells to secrete insulin. In DM sufferers, physical activity is the main treatment for controlling blood sugar levels, one of which is the PERSADIA Series 1 Gymnastics which is a weight lifting exercise designed to increase muscle eccentricity which aims to increase glucose tolerance and reduce HbA1c. However, until now it is not known for sure the effect of PERSADIA Series 1 Gymnastics on reducing fasting blood sugar in women with Diabetes Mellitus. This study aims to determine and analyze the effect of PERSADIA Series 1 Gymnastics on reducing fasting blood sugar levels in women with Diabetes Mellitus. This research is a quasi-experimental type and was designed using a pre and post test group design with a control group. This study was followed by 60 women with Diabetes Mellitus and divided into 30 control groups who consumed OAD and carried out unstructured activities and 30 intervention groups who consumed OAD and did PERSADIA Series 1 Gymnastics which were carried out 3 times a week for a total of 12 times for 4 weeks with each training session lasting 40 minutes. Fasting blood sugar examination was carried out at the beginning and at the end of the study with subjects fasting at least 10 hours before the test. The research was processed using the SPSS 26 statistical test. Fasting blood sugar levels in both the control and intervention groups had an increase from pre-test GDP to post-test GDP. Statistically, there were no significant differences before and after the test in the control or intervention groups and also when the data between groups was compared with a p value = 0.403. PERSADIA Gymnastics Series 1 has not been able to significantly reduce fasting blood sugar levels in women with Diabetes Mellitus.